Are Malaysians getting fatter and rounder?: an updated systematic review (2009 – 2015) - Tan, Siew Tin; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Ibrahim, Normala; Tan, Kit Aun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Overweight and obesity have become a serious health issue in worldwide and Malaysia is no exception. In view that obesity is one of the leading causes of non-communicable diseases, this systematic review aimed to explore whether Malaysian are getting fatter (overweight or obesity) and rounder (abdominal obesity). Searches of the published literature were conducted using 3 databases including EMBASE, MEDLINE, and PubMed. These were limited to cross-sectional or cohort studies in Malaysia. The databases provided the prevalence of overweight, obesity, and abdominal obesity among 15 years old and above Malaysian population from 2009 to 2015. In total, 47 articles were included in this review. Findings exhibit that the prevalence rates of overweight, obesity, and abdominal obesity range from 9.5% to 43.5%, 1.77% to 26.4% and 11.4% to 57.4%, respectively. Overweight is more predominant among males. However, obesity and abdominal obesity are more predominant among females. This means that more females are getting fatter and “rounder” as compared to males in Malaysia. The findings imply a lack of intervention programmes based on proper randomized controlled trials which are needed to adequately address the problem of obesity in Malaysia.